Association of fibroblast growth factor (FGF-21) as a biomarker with primary mitochondrial disorders, but not with secondary mitochondrial disorders (Friedreich Ataxia) - Salehi, Mohammad Hossein; Kamalidehghan, Behnam; Houshmand, Massoud; Aryani, Omid; Sadeghizadeh, Majid; Mossalaeie, Mir Majid (Molecular biology reports, 2013)
Mitochondrial respiratory chain deficiencies are a group of more than 100 disorders of adults and children, with highly variable phenotypes. The high prevalence of mitochondrial disorders (MIDs) urges the clinician to diagnose these disorders accurately, which is difficult in the light of highly variable and overlapping phenotypes, transmission patterns and molecular backgrounds. Fibroblast growth factor 21 (FGF-21) is an important endocrine and paracrine regulator of metabolic homeostasis. The FGF-21 transcript is reported to be abundantly expressed in liver, but little is known about the regulation of FGF-21 expression in other tissues. FGF-21 could play a role in the metabolic alterations that are often associated with mitochondrial diseases. The aim of this study was to show the association of the FGF-21 biomarker with human primary MIDs and secondary MIDs in suspected patients in Iran. Serum FGF-21 levels were determined using ELISA in 47 mitochondrial patients, including 32 with primary MIDs, 15 patients with Friedreich ataxia as a secondary MID and 30 control subjects. Serum FGF-21 levels were significantly higher in subjects with the primary MIDs ( p < 0.05), compared to subjects without MIDs. However, serum FGF-21 levels did not show significant increase in subjects with FA as a secondary MID. There is an association between increasing concentrations of FGF-21 with mitochondrial diseases, suggesting FGF-21 as a biomarker for diagnosis of primary MIDs in humans. However, this biomarker is not appropriate for the diagnosis of FA.